Steady state temperature distribution in Human Skin during burn injury using The Finite Element Method with Bio-Heat Equation. - Md. Matiar Rahman; Nazmun Nahar Papri; Mridul Sannyal; Abul Mukid Mohammad Mukaddes; Aminur Rahman Khan (Journal of Science, 2025)
Human skin is exposed to high thermal energy due to solar radiation, contact of a hot disk, contact of hot fluid etc. This high thermal energy may result in the thermal burn. Depending upon the excess thermal energy and exposure duration, burn injury can be severe and may lead to damage of the skin. Prior knowledge of the temperature distribution in the skin burn is thus necessary for the proper treatment of the skin burn injuries. In this study a 2D Finite Element (FE) model of human skin in contact with a heating disk is developed. Natural convection to ambient air and evaporation boundary condition is considered to the area that is not in direct contact with the heating disk. Whether, temperature boundary condition is considered at the body core. A C-code is developed for the solution of the finite element model. Linear and quadratic triangular element is used for the analysis. FEM result was compared with commercial numerical solver (COMSOL-Multiphysics) and boundary element method. A good agreement was found. Both steady and transient temperature is measured. The effect of various parameters i.e. ambient temperature, ambient heat transfer coefficient, blood perfusion, evaporation rate, disk temperature is briefly discussed.